Twenty-five year record of chemicals in open field precipitation and throughfall from a medium-altitude forest catchment (Strengbach - NE France): An obvious response to atmospheric pollution trends. (1st April 2019) - Pierret, Marie-Claire; Viville, Daniel; Dambrine, Etienne; Cotel, Solenn; Probst, Anne
Abstract: This study concerned a 25 yr continuous record of bulk precipitation and throughfall composition in a medium-altitude forested environment. The 1986–2012 survey from the more intense acid rain period in the mid-eighties until the present allowed the quantification of the interaction between atmospheric deposition and vegetation and the long-term evolution following pollutant emission trends. The long-term monitoring evidenced some significant temporal trends (pH, conductivity, SO4 2−, Cl −, NO3 −, Ca 2+, Mg 2+, and K + ). Significant decreases in the concentrations and fluxes of several ions were observed (H + and SO4 2−, Cl −, and Ca 2+ ) in open field precipitation and throughfalls. The regular and strong decrease in protons and sulfate followed the decreases in anthropogenic SO2 and NOx (proton precursors) since the 1980s. The decrease in Cl − concentrations was weaker and could have been related to the regional reduction in HCl emissions and/or to changes in the precipitation regime. The annual calcium fluxes were reduced from approximately 15 to 9 and 6 to 2 kg ha −1 under spruces and beeches, respectively, as a consequence of reductions in anthropogenic industrial dust. In such calcium-limited resource soils, the atmospheric Ca flux exceeded the Ca flux from mineral weathering and was highly bioavailable for vegetation growth. This decrease in nutrient input had strong consequences for soil nutrients and may thus have participated in forest decline. The two tree plantations had contrasting effects on the physico-chemical parameters of the incoming precipitation with higher water interception and chemical concentrations under spruces than under beeches, which underlined the role of tree species in atmospheric inputs to soils. The structure and persistence of spruce needles enhanced the capture of particles and water, accentuating the acidity of the deposition and leading to the intensification of acidification processes, nutrient leaching in soils and forest decline. In contrast, beech leaves were able to neutralize a portion of the atmospheric protons, which minimized and reduced the negative effects of acid rain. In addition, the throughfalls represented an important part of the biological cycle of trees for some elements such as K or N, as indicated by the contrasting patterns at year and long-term scales regarding the vegetation type. However, our study indicated that the influence of tree species might change over time with changes in atmospheric pollution, in precipitation regime, or in stand structure. This study outlined the importance of the long-term record of open field precipitation and throughfalls under various tree types to better evaluate the real inputs of elements to forest ecosystems and among them, essential mineral nutrients. Graphical abstract: Image 1 Highlights: 1986–2012: a 2.5-decade survey of atmospheric deposition in the Vosges Mountains. The sulfate decrease in precipitation and throughfall matched that of SO2 emissions. The strong Ca decrease was related to changes in anthropogenic and natural sources. Beeches and spruces modified the atmospheric inputs to soil differently with time. N depositions decrease in OFP and under beech but increase under spruce.